Strategi True Or False Untuk Meningkatkan Partisipasi Belajar Pkn Siswa Kelas IV SD - Prima Susi Diarti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
This study is encouraged by the low marks of grade IV students at SDN 25 Batang Anai in Civic Education subject, including do discussion, propose ideas, and make conclusion. It was caused by learning that students used to experience, i.e. expository method. This study is aimed to improve students’ learning participation, especially in doing discussion, proposing ideas, and making conclusion. This is a classroom action research with two cycles. Data were collected through observation and test. Result of this study shows that true or false strategy can improve students’ learning participation. In cycle I, average score percentage of students in doing discussion is 58.92%; 49.80% for proposing ideas; and 33.92% for making conclusion. Meanwhile in cycle II, learning participation gets improvement. Average score percentage of students in doing discussion becomes 84.45%; 77.73% for proposong ideas; and 75.95% for making conclusion.